Bureaucracy and Foreign Policy: the New Challenges of Diplomatic Practice - Carreño Lara, Eduardo (Revista del CLAD Reforma y Democracia, 2016)
The international order is based largely on State sovereignty. However, nowadays this principle has been affected by the emergence of international regimes that rule state behavior in different areas: human rights, international trade, environmental degradation, information technology, international security, and so forth. In this context, neither governments nor international organizations are able by themselves to address the complexities of international system. Therefore, business and civil society have become important actors in almost all areas of world politics. Their active participation is a critical component, if not essential, in the implementation of global public policies. So, the aim of this article is to analyze not only the standard structures of the ministries of foreign affairs, but also how they respond to the necessity to interact with other public institutions and NGOs. In doing so, it is possible to establish how governments determine their diplomatic skills to tackle global changes. In sum, global governance requires a deep transformation of traditional bureaucratic organizations, as well as, the construction of a flexible and results-oriented organizational culture. In this sense, throughout professionalization of diplomats and foreign policy’s staff seems to be demanded by governments whose expectations have changed.
Keywords: Bureaucracy; Foreign Policy; Governance; Diplomacy; Public Administration